Innovation in traditional Trás-os-Montes products: consumer perception on extra-long maturation sheep cheese - Mendonça, Álvaro (2018)
Cheese is an important food for a healthy diet. Portugal is a country with a huge tradition in the manufacture of cheese from the use of small ruminants. Herds managed in production systems based on pastoralism, with cycles of production according to animal physiology, shaped by the time and the expertise of the shepherd. The production of traditional cheeses is a very strong habit in rural communities and the study of consumer acceptance of matured cheese is an important factor for the valorization/competitiveness strategy. This work is based on data from a survey on the consumption preferences of Extra Long Maturation (ELM) sheep's cheese. The objective of the study was to identify the consumer profile, cheese consumption habits and to compare consumers' perception about the characteristics of cheeses with different maturation periods (6, 11 and 12 months).